Anxiety in Pregnant Women During Coronavirus (Covid-19) Pandemic in East Java, Indonesia - Zakkiyatus Zainiyah; Eny Susanti (Faculty of Medicine, Universitas Padjadjaran, 2020)
The 2019 coronavirus pandemic has been recognized as a trigger for anxiety, especially in pregnant women. Pregnant women are among those with a high-risk for contracting coronavirus, not only for themselves but also for the unborn child. Continuous information is needed for pregnant women to avoid anxiety because anxiety will result in complications for both mother and child, such as low birth weight baby and postpartum psychological disorder. The purpose of this study was to identify the prevalence of anxiety in pregnant women during the Coronavirus pandemic in Madura, East Java, Indonesia. This study was a cross-sectional descriptive study conducted from April 13 to May 8, 2020. Data were collected using a Google form distributed to all pregnant women in the Madura Region based on the list of pregnant women from the midwives in each city in this region. Seventy pregnant women returned the completed form, and data were analyzed using frequency tables and percentages. Results showed that 31.4% of pregnant women experienced very severe anxiety, 12.9% experienced severe anxiety, and the remainings did not experience anxiety. In conclusion, the coronavirus pandemic indeed increases anxiety in pregnant women which will need to be addressed to avoid negative impacts on the mother and unborn child. Counseling is needed to reduce anxiety by asking the women to stay at home, wash their hands, wear masks, eat nutritious food, have their pregnancy checked, perform exercise for pregnant women at home, and seek for help when facing emergencies. Tingkat Kecemasan Ibu Hamil pada Masa Pandemi Viruscorona (Covid-19) di Jawa Timur, Indonesia Pandemi virus corona 2019 ini menyebabkan kecemasan, terutama pada ibu hamil, karena ibu hamil merupakan kelompok risiko tinggi untuk tertular virus corona, terutama pada janin yang dikandungnya, sehingga diperlukan informasi secara terus menerus kepada ibu hamil supaya tidak terjadi kecemasan, karena kecemasan ini akan berakibat komplikasi pada ibu dan janinnya. Dampak kecemasan pada ibu hamil dan janin adalah Berat Badan Lahir Rendah dan gangguan psikologis pada ibu setelah melahirkan. Tujuan penelitian ini mengidentifikasi tingkat kecemasan ibu hamil di masa pandemi virus Corona di wilayah Madura, Jawa Timur. Penelitian ini dilakukan tanggal 13 April sampai dengan 8 Mei 2020 dan merupakan penelitian desktriptif dengan menggunakan google form yang disebarkan ke seluruh ibu hamil di Wilayah Madura melalui bidan yang ditunjuk setiap kota yang ada di Madura. Tujuh puluh ibu hamil mengembalikan formulir yang telah diisi dan data dianalisis menggunakan tabel frekuensi dan persentase. Hasil penelitian menunjukkan bahwa 31.4% mengalami kecemasan sangat berat, 12.9% mengalami kecemasan berat, dan sisanya ibu tidak mengalami kecemasan atau dalam keadaan normal. Simpulan, pandemi virus corona memang meningkatkan kecemasan pada ibu hamil yang perlu diatasi untuk menghindari dampak negatif pada ibu dan janinnya. Konseling diperlukan untuk mengurangi kecemasan dengan meminta ibu-ibu untuk tinggal di rumah, mencuci tangan, memakai masker, makan makanan bergizi, memeriksakan kehamilannya, melakukan senam ibu hamil di rumah, dan mencari pertolongan saat menghadapi keadaan darurat.